2010
DOI: 10.2991/ijcis.2010.3.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Computing with Words in Risk Assessment

Abstract: This paper presents a comprehensive overview of currently known applications of computing with words (CWW) in risk assessment. It is largely grouped into the following 5 categories: (1) fuzzy number based risk assessment; (2) fuzzy rule-based risk assessment; (3) fuzzy extension of typical probabilistic risk assessment; (4) ordinal linguistic approach for risk assessment; and (5) miscellaneous applications. In addition, the role of CWW within the broad area of risk assessment is briefly characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 225 publications
(208 reference statements)
0
6
0
Order By: Relevance
“…As the assembly works out, a separate heading for risk familiar proof process strength is not good because the information and sequence are forced [9]. In China's PPP ventures, almost all key risk items are at a national or production intensity rank, linked to monetary, subsequent, and legal circumstances [10].…”
Section: Introductionmentioning
confidence: 99%
“…As the assembly works out, a separate heading for risk familiar proof process strength is not good because the information and sequence are forced [9]. In China's PPP ventures, almost all key risk items are at a national or production intensity rank, linked to monetary, subsequent, and legal circumstances [10].…”
Section: Introductionmentioning
confidence: 99%
“…11 Additionally, there currently is no general approach to construct reasonable membership functions. 43 However, many researchers have used the fuzzy set theory for risk analysis, and the former studies have shown that the fuzzy approaches are effective methods in risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Risk is a measure of injury or loss related to human activity. 43 Many workers are at risk of harm from work for a variety of reasons. Workplace accidents increase the costs of social healthcare and insurance systems.…”
Section: Risk Analysis and Assessment Methodsmentioning
confidence: 99%
“…In fields such as: situation awareness, information retrieval [5], risk assessment [6,7,8], engineering evaluation [9], decision making [10,11,12,13], sensory evaluation [14,15], data mining [16], and social choice [2], human interact with natural language (e.g. words).…”
Section: B Cww = Fuzzy Logicmentioning
confidence: 99%